Seismic imaging of the Scandinavian Caledonides to define ICDP drilling sites - Hedin, P.; Juhlin, Christopher; Gee, D. (2012)
A 36 kilometer long high resolution 2D seismic reflection profile was acquired in the summer of 2010 to be used in the planning of the COSC (Collisional Orogeny in the Scandinavian Caledonides) Deep Drilling Project. Two fully cored boreholes, each to c. 2.5. km depth, are planned for the Åre-Mörsil area of west-central Sweden in order to increase our understanding of orogenic processes and, in particular, the tectonic evolution of the Scandinavian Caledonides. Besides providing important sub-surface structural information in the vicinity of the potential drill sites, the seismic profile also provides detailed, high resolution images previously not available for the uppermost few kilometers in the region. The subsurface is highly reflective and very complex down to at least 9. km depth (the limit of decoded data) with clear reflections spanning the entire length of the profile. Correlation with previous regional reflection seismic and magnetotelluric surveys has been achieved by acquisition of a short (7. km) connecting profile. A clearly defined reflection, present in the new profile at depths between c. 2.5. km in the east and c. 4.5. km in the west and with an average westwards dip of c. 3.5°, apparently defines the base of the Lower Allochthon. Closer to the Caledonian front, this sole thrust overlies the Cambrian alum shale formation, which rests unconformably on the autochthonous Precambrian crystalline basement. The latter is remarkable for its deep internal reflectivity which is probably related to mafic intrusions in a dominantly granitic host-rock; their deformation may be of both Caledonian and older (e.g. Sveconorwegian) age. The new high resolution seismic data provide the basis for locating the first borehole in the Seve Nappe Complex. They also demonstrate that the second hole, designed to penetrate the Caledonian basement, will have to be located further east than was originally planned. © 2012 Elsevier B.V.